2023
DOI: 10.1039/d2tc05321g
|View full text |Cite
|
Sign up to set email alerts
|

IrAu12superatom modified by chiral diphosphines: doping-induced enhancement of chiroptical activity

Abstract: Gold superatoms modified by chiral ligands are a new class of chiroptical nanomaterials, but improvement of their chiroptical properties such as circular dichroism (CD) and circularly polarized luminescence (CPL) remains...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…The hydride NBO charges in 2 and 3 (∼−0.3) approach that of their counterpart in [PtHAg 19 (dtp/dsep) 12 ] . This charge distribution, together with the significant Rh–Ag ico Wiberg bond indices and the non-negligible Ag ico –Ag ico Wiberg bond indices (larger than the mainly argentophilic Ag ico –Ag cap ones) are consistent with the view of 1 , 2 , and 3 being made of eight-electron centered-icosahedral [Rh@Ag 12 ] 3+ , [RhH@Ag 12 ] 4+ , and [RhH 2 @Ag 12 ] 5+ cores stabilized by 12 dtp – and 9, 8, and 7 Ag + centers, respectively. ,, ,,,, The Kohn–Sham orbital diagrams of the three NCs (Figures and S29–S31) support this view, with their three highest occupied orbitals that can be identified as the 1P superatomic orbitals and their five lowest vacant ones as the 1D levels, a situation corresponding to the expected 1S 2 1P 6 1D 0 superatomic closed-shell configuration . Due to the presence of one and two encapsulated hydrides in 2 and 3 , respectively, the superatomic orbitals are, respectively, axially and planarly distorted away from regular spherical symmetry.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The hydride NBO charges in 2 and 3 (∼−0.3) approach that of their counterpart in [PtHAg 19 (dtp/dsep) 12 ] . This charge distribution, together with the significant Rh–Ag ico Wiberg bond indices and the non-negligible Ag ico –Ag ico Wiberg bond indices (larger than the mainly argentophilic Ag ico –Ag cap ones) are consistent with the view of 1 , 2 , and 3 being made of eight-electron centered-icosahedral [Rh@Ag 12 ] 3+ , [RhH@Ag 12 ] 4+ , and [RhH 2 @Ag 12 ] 5+ cores stabilized by 12 dtp – and 9, 8, and 7 Ag + centers, respectively. ,, ,,,, The Kohn–Sham orbital diagrams of the three NCs (Figures and S29–S31) support this view, with their three highest occupied orbitals that can be identified as the 1P superatomic orbitals and their five lowest vacant ones as the 1D levels, a situation corresponding to the expected 1S 2 1P 6 1D 0 superatomic closed-shell configuration . Due to the presence of one and two encapsulated hydrides in 2 and 3 , respectively, the superatomic orbitals are, respectively, axially and planarly distorted away from regular spherical symmetry.…”
Section: Resultssupporting
confidence: 73%
“…Ligand-protected nanoclusters (NCs) with precise atomic and geometric arrangements have gained attention owing to their unique physicochemical properties. Their electronic structures, whose shapes are reminiscent of the conventional atomic orbitals, can be conceptualized by the superatom model . Following the discovery of several stable eight-electron superatoms , altering the physicochemical properties of clusters through heterometal doping has become a topical research project in recent years. One of the broadly studied targets, the centered icosahedral [Au 13 ] 5+ , which is protected by diphosphines and halides, has successfully been doped by group 8–10 metals at its center, maintaining the eight-electron count, and there is evidence that the dopant significantly affects the photophysical properties. , Interestingly, when doping the thiolate-protected [Ag 25 ] 17+ framework with a group 9 metal, the actual dopant is MH and not M (M = Rh or Ir). Very recently, the same group showed that when using a group 8 metal, the actual dopant is MH 2 (M = Ru, Os) .…”
Section: Introductionmentioning
confidence: 99%
“…15(a)). [81][82][83][84][85][86] Because the molecular orbitals of such ligand-protected metal nanoclusters have analogous shapes to atomic orbitals (s, p, d,. .…”
Section: Inorganic Nanocluster Sensitizersmentioning
confidence: 99%
“…, by heterometal doping 26–29 ), and optical properties ( e.g. , NIR emission 6,7,30 and chiroptical activity 31–33 ), as well as further expansion of their potential applications ( e.g. , photodynamic catalysis and nano-electronic devices).…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] It is therefore of importance to study the inuencing factors in depth on the geometric and electronic structures of the individual icosahedral Au 13 clusters. In this context, the past 15 years have rst witnessed a renewed interest in the typical phosphine-protected Au 13 clusters involving development of new synthetic routes (e.g., HCl-induced convergence), 6,7,22,23 exploration of formation mechanisms, 24,25 tuning of electronic properties (e.g., by heterometal doping [26][27][28][29] ), and optical properties (e.g., NIR emission 6,7,30 and chiroptical activity [31][32][33] ), as well as further expansion of their potential applications (e.g., photodynamic catalysis and nano-electronic devices). 34,35 More recently, comparative studies on several new types of Au 13 analogues protected by other pnictines (e.g., functionalized diphosphine, 36 phosphinous acid, 37 diarsine, 38 and monostibine [39][40][41] ) or mimics of pnictine (N-heterocyclic carbenes) [42][43][44][45][46][47] have also been extensively made both experimentally and theoretically.…”
Section: Introductionmentioning
confidence: 99%